On Multiple Twisted p-adic q-Euler ζ-Functions and l-Functions - Min-Soo Kim; Taekyun Kim; Jin-Woo Son (Abstract and Applied Analysis)
We give the existence of multiple twisted p-adic q-Euler ζ-functions and l-functions, which are generalization of the twisted p-adic (h,q)-zeta functions and twisted p-adic (h,q)-Euler l-functions in the work of Ozden and Simsek (2008).